Rapid pole-to-pole oscillation of a protein required for directing division to the middle of Escherichia coli - Raskin, David M. (The National Academy of Sciences, 1999)
Accurate placement of the division septum at the midpoint of Escherichia coli cells requires the combined action of a general division inhibitor (MinC), a site-specific suppressor of division inhibition (MinE), and an ATPase (MinD) that is required for proper functioning of both MinC and MinE. We previously showed that a functional MinE-Gfp fusion accumulates in a ring structure at/near the middle of cells. Here we show that functional Gfp-MinD accumulates alternately in either one of the cell halves in what appears to be a rapidly oscillating membrane association-dissociation cycle imposed by MinE. The results indicate that MinD represents a novel type of dynamic cellular element in bacteria, with multiple roles in directing the division apparatus to the middle of the cell.